ChemInform Abstract: Synthesis of N‐Sulfonylamidines by Catalyst‐Free Hydroamination of Ynamides and Amines. Issue 26 (1st July 2014) - Kong, Yulong; Yu, Lian; Cui, Yuming; Cao, Jian
Abstract Alkyl amines react with ynamides under mild conditions, whereas aromatic amines require higher temperatures and the presence of triethylamine.